Expression of thermostable α-amylase using formaldehyde dehydrogenase promoter in Meyerozyma guilliermondii strain SO - Mohamad Nasir, Nurul Syazwani (2018)
α-amylase is an enzyme that breakdown starch or glycogen to release simple molecules such as maltose and glucose. SR74 α-amylase produced from the Geobacillus stearothermophilus SR74 has huge potential for commercialization for industrial applications due to its thermostable and thermoactive properties. However, its expression in wild type host is too low. Thus, it was cloned and expressed in two expression systems namely, bacteria and yeast. Its expression in Escherichia coli was accompanied with the formation of inclusion bodies. The drawbacks of E. coli expression system were overcome by the Pichia pastoris expression system. However, SR74 α-amylase expression in P. pastoris under alcohol oxidase promoter (PAOX) required longer fermentation time and high methanol consumption. Therefore, there is a need for a new expression system that can overproduce α-amylase extracellularly without methanol induction with shorter fermentation time. This study aims to express SR74 α-amylase in a newly developed yeast expression system, Meyerozyma guilliermondii strain SO using formaldehyde dehydrogenase promoter (PFLD). Initially, an integration site of pFLDα in M. guilliermondii strain SO genome was predicted, followed by cloning and expression of α-amylase using PFLD. Then, the α-amylase production in M. guilliermondii strain SO was optimized. FLD gene was determined and isolated with the help of hmmer3.1b-2 (HMM) software for prediction of integration site. Based on nucleic acid sequence analysis, it was confirmed that pFLDα was able to integrate at PFLD loci in M. guilliermondii strain SO genome. Then, SR74 α-amylase gene was cloned into pFLDα followed by transformation into M. guilliermondii strain SO. Colony PCR, α-amylase screening plate and western blot analysis proved that SR74 α-amylase was successfully cloned and expressed in M. guilliermondii strain SO. Qualitative (screening plate) and quantitative screenings (Dinitrosalicylic acid assay) for recombinant α-amylase production were performed to assess the activity of recombinant α-amylase under PFLD regulation. Optimization of extracellular SR74 α-amylase production (assayed at 65 °C) in M. guilliermondii strain SO found that the highest expression was 26 U/mL at 24 h, without methanol induction. The yield was 16-fold higher than the wild-type. G. stearothermophilus SR74 and was comparable to the P. pastoris system at 5.17 times faster without methanol induction. In conclusion, the SR74 α-amylase has successfully been expressed in this newly expression with shorter cultivation time and without inducer requirements at comparable yield than established P. pastoris expression system. Shorter time and no inducer requirement were expected to significantly reduce the cost of production. The optimization procedure by Response Surface Methodology (RSM) software, mutational study and in-depth study on PFLD regulation were suggested to increase the production and to make the enzyme more favorable to industrial application.